2005
DOI: 10.1177/154405910508401115
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Heritability for Dental Caries Traits

Abstract: The role of genetic and environmental factors on dental caries progression in young children was determined. A detailed caries assessment was performed in 2 examinations on 314 pairs of twins initially 1.5 to 8 years old. Surface-based caries prevalence rates (SBCPR) and lesion severity (LSI) were computed. Heritability estimates were calculated by SOLAR software. Analyses were performed on all ages combined and by age group (1.5-< 4; 4–6; > 6). Overall heritability estimates (H) of net increments SBCPRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 22 publications
1
91
0
1
Order By: Relevance
“…Indeed, 40-65% of caries risk has been attributed to this factor (Bretz et al, 2005). Recent studies have confirmed that the caries susceptibility of a patient may be determined by their DNA (Burgner et al, 2006;Patir et al, 2008;Peres et al, 2010;Werneck et al, 2010;Kang et al, 2011;Stanley et al, 2014), in addition to the well-known environmental factors involved in caries risk such as bacteria, diet, oral hygiene, and host factors (Lenander-Lumikari and Loimaranta, 2000;Nariyama et al, 2004;Zero, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 40-65% of caries risk has been attributed to this factor (Bretz et al, 2005). Recent studies have confirmed that the caries susceptibility of a patient may be determined by their DNA (Burgner et al, 2006;Patir et al, 2008;Peres et al, 2010;Werneck et al, 2010;Kang et al, 2011;Stanley et al, 2014), in addition to the well-known environmental factors involved in caries risk such as bacteria, diet, oral hygiene, and host factors (Lenander-Lumikari and Loimaranta, 2000;Nariyama et al, 2004;Zero, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This disease can cause dental pain, tooth loss, and more severe systemic disease (Mattila et al, 1995;Petersen, 2003). Studies of twins (Shuler, 2001), families and animal breeding (Hunt, 1944;Klein, 1946), and genomics (Shelling and Ferguson, 2007) indicated that dental caries has an important genetic component and that 40-65% of caries risk may be related to genetic factors (Bretz et al, 2005). It has been widely established that dental caries is mostly influenced by environmental factors such as microbial, diet, oral hygiene, and host aspects (LenanderLumikari et al, 2000;Petersen, 2003;Nariyama et al, 2004); however, there is increasing evidence for a genetic component in caries susceptibility (Patir et al, 2008;Azevedo et al, 2010;Ozturk et al, 2010;Kang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on monozygotic twin pairs reared apart suggest a genetic contribution to caries of 40% [Conry et al, 1993]. Studies of twins reared together estimated the heritability for caries, adjusted for age and gender, as 45-64% [Bretz et al, 2005]. However, shared behavior, practice, and habits within families can be expected to contribute to covariance between relatives and to mimic genetic correlation if not controlled by the experimental design [Potter, 1990].…”
mentioning
confidence: 99%